A Note on the Indonesian Sub-National Government Surplus, 2001-2006 - Lewis, Blane D. (World Bank, Washington, DC, 2017)
The Indonesian government has devolved significant expenditure authority to sub-national units since 2001. New sub-national government expenditure assignments have been paid for by a substantial increase in intergovernmental transfers to lower levels of government. The center has decided against devolving any significant new tax authority to the regions, at least for the time being. This note examines some fundamental issues related to these unspent funds. The paper has two particular objectives. First, the paper describes the basic features of sub-national government surplus and reserves since decentralization, including their size and spatial distribution. Second, it seeks to explain the observed variation in surplus across sub-national governments, according to some standard hypotheses. The paper proceeds as follows. First, some basic information regarding the buildup and geographic distribution of sub-national reserves is offered. Second, the methodological approach to the study of sub-national government surpluses is detailed. Third, the results of the econometric examination are presented and discussed. Finally, the note closes with a summary of the main findings and a proposal for some additional research that might be useful in the continuing development of central policy in this area.